2014
DOI: 10.1186/1471-2164-15-336
|View full text |Cite
|
Sign up to set email alerts
|

Secretome analysis reveals effector candidates associated with broad host range necrotrophy in the fungal plant pathogen Sclerotinia sclerotiorum

Abstract: BackgroundThe white mold fungus Sclerotinia sclerotiorum is a devastating necrotrophic plant pathogen with a remarkably broad host range. The interaction of necrotrophs with their hosts is more complex than initially thought, and still poorly understood.ResultsWe combined bioinformatics approaches to determine the repertoire of S. sclerotiorum effector candidates and conducted detailed sequence and expression analyses on selected candidates. We identified 486 S. sclerotiorum secreted protein genes expressed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
187
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(203 citation statements)
references
References 78 publications
13
187
0
Order By: Relevance
“…Moreover, we demonstrate that the majority of these CSEPs are among the most highly expressed fungal genes in green brooms (Table 2), whereas essentially no expression of these effectors is observed under in vitro conditions or in the necrotrophic stage of the disease (Figure 10). In agreement with these findings, high transcript levels in planta have been used as a filter to identify effectors in other filamentous pathogens (Pedersen et al, 2012;Guyon et al, 2014). This high abundance of effectors may allow these proteins to efficiently interact and interfere with their host targets.…”
Section: Perniciosa Biotrophic Infection Involves the Transcriptiomentioning
confidence: 67%
“…Moreover, we demonstrate that the majority of these CSEPs are among the most highly expressed fungal genes in green brooms (Table 2), whereas essentially no expression of these effectors is observed under in vitro conditions or in the necrotrophic stage of the disease (Figure 10). In agreement with these findings, high transcript levels in planta have been used as a filter to identify effectors in other filamentous pathogens (Pedersen et al, 2012;Guyon et al, 2014). This high abundance of effectors may allow these proteins to efficiently interact and interfere with their host targets.…”
Section: Perniciosa Biotrophic Infection Involves the Transcriptiomentioning
confidence: 67%
“…S. sclerotiorum may also secrete effector proteins, such as S. sclerotiorum INTEGRIN-LIKE and S. sclerotiorum CHORISMATE MUTASE1, to diminish plant defense responses (Kabbage et al, 2013;Zhu et al, 2013). A recent bioinformatic study revealed that the S. sclerotiorum genome encodes a large set of candidate effector proteins (Guyon et al, 2014), which may have functions in Sclerotinia spp. pathogenesis.…”
mentioning
confidence: 99%
“…As one of the most devastating and cosmopolitan fungal pathogens, S. sclerotiorum has developed various effective ways to invade host plants that mainly involve the secretion of oxalic acid [4e9] and enzymes that degrade the cell wall [10e16]. In recent years, S. sclerotiorum has been predicted and proven to secrete low-molecular-weight proteins that function as potential effectors and suppress host resistance [17] and [18]. In addition to these important pathogenicity factors, many others involved in the development and pathogenicity of S. sclerotiorum have been identified and characterized at the molecular level [19e27].…”
Section: Introductionmentioning
confidence: 99%